Neuroendocrine Neoplasms of the Breast: Current Insights and Future Directions - Lei Jiang; Xinyuan Pan; Zhiqiang Lang (Cancer Reports)
ABSTRACT Background The breast neuroendocrine neoplasms (NENs) represent a heterogeneous group of tumors and account for less than 1% of all NENs. The 5th edition of the WHO Classification of Breast Tumors in 2019 introduced a more stringent definition for breast NENs including neuroendocrine tumors (NETs) (G1, G2) and neuroendocrine carcinomas (NECs) (small cell carcinoma, large cell neuroendocrine carcinoma). While the diagnostic criteria and treatment of breast NENs still have some unsolved issues. Objective We aim to discuss the diagnosis, treatment progress, existing problems, and future development direction of breast NENs. Methods We provide a comprehensive review and evaluation of the diagnostic criteria, pathological features, utilization of immunohistochemical markers, molecular characteristics, pathogenesis, clinical significance, treatment options for breast NENs. Results (1) Under the new definition, "pure" breast NENs are extremely rare. (2) Breast NETs are graded according to Nottingham grading System. Grading criteria utilized in other systems for NENs, such as mitotic count, ki67 proliferation index, and necrosis, have not been applied to breast NENs. (3) The WHO has not yet acknowledged the existence of NET G3 clearly. (4) The expression of NE markers may differ in breast NECs. (5) The treatment of breast NENs is still based on IBCs‐NST, and without any difference from invasive carcinoma with NE features. (6) The prognosis of breast NENs remains unclear, while the prognosis for NECs is significantly poorer than invasive breast carcinomas of no special type (IBCs‐NST) has been confirmed. Conclusion Strict adherence to criteria is the key to correctly diagnose breast NENs with the exclusion of metastasis from other sites. Further exploration is required to determine the tissue origin of breast NENs and understand the pathogenesis. Efforts are still needed to establish unified diagnostic criteria and a unique diagnosis and treatment consensus for breast NENs.